The Problem with the Implementation of Cooperative Learning in Speaking Classes for Elementary School - Anissa Salsabilla; Ardya Rigita Cahyani; Rabbyani Ramaita Rahmah; Yulia Fuji Astuti; Izzah Supeni (Indonesian Journal of Elementary Education and Teaching Innovation, 2022)
Despite the well-established benefits of cooperative learning, implementation remains a challenge. This research aims to know the problems teachers face in implementing cooperative learning in speaking classes in elementary school. This study used a qualitative design with an interview approach with teachers to investigate problems in implementing cooperatives. This study report involves one teacher who has participated and has implemented cooperative learning for at least three years. The current study uses the interview data collection method to investigate the implementation of cooperative learning in MI TPI Keramat. The result indicates some problems the teacher faced in implementing cooperative learning in the classroom. The main problem faced by students in cooperative learning is group conflict.Keyword :  cooperative learning, speaking class, elementary school